2012
DOI: 10.1186/1756-3305-5-136
|View full text |Cite
|
Sign up to set email alerts
|

Vector capacity of Anopheles sinensis in malaria outbreak areas of central China

Abstract: BackgroundBoth falciparum and vivax malaria were historically prevalent in China with high incidence. With the control efforts, the annual incidence in the whole country has reduced to 0.0001% except in some areas in the southern borders after 2000. Despite this, the re-emergence or outbreak of malaria was unavoidable in central China during 2005–2007. In order to understand the role of the vector in the transmission of malaria during the outbreak period, the vector capacity of An. sinensis in Huanghuai valley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Similar to several studies [39][40] that showed a negative correlation between livestock and malaria vector, this study also found a negative effect from the livestock on An. sinensis .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to several studies [39][40] that showed a negative correlation between livestock and malaria vector, this study also found a negative effect from the livestock on An. sinensis .…”
Section: Discussionsupporting
confidence: 90%
“…A study suggested that increased vector capacity of An. sinensis related with the mosquito host reduction (livestock), and human behavioural change contributed to P. vivax malaria outbreak in Huaiyuan county of Anhui province [45]. This area, especially north of the Huai River, is one of the high-risk areas with unstable malaria transmission [46], possibly due to environmental conditions associated with geographical location [11, 14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…A primary reason is that the local predominant anopheline species is A. sinensis , which is refractory to P. falciparium ( 11 , 12 ). …”
Section: Discussionmentioning
confidence: 99%